Transições de fase de não equilíbrio em redes de Kleinberg - Santos, Thiago Bento dos (2017)
We study through Monte Carlo simulations and finite-size scaling analysis the nonequilibrium phase transitions of the majority-vote model and the contact process taking place on spatially embedded networks. These structures are built from an underlying regular lattice over which long-range connections are randomly added according to the probability, Pij ~ rα , where rij is the Manhattan distance between nodes i and j, and the exponent α is a controlling parameter [J. M. Kleinberg, Nature 406, 845 (2000)]. Our results show that the collective behavior of those systems exhibits a continuous phase transition, order-disorder for the majority-vote model and active-absorbing for the contact process, at a critical parameter, which is a monotonous function of the exponent α. The critical behavior of the models has a non-trivial dependence on the exponent α. Precisely, considering the scaling functions and the critical exponents calculated, we conclude that the systems undergoes a crossover between distinct universality classes. For α ≤ 3 the critical behavior in both systems is described by mean-field exponents, while for α ≥ 4 it belongs to the 2D Ising universality class for majority-vote model and to Directed Percolation universality class for contact process. Finally, in the region where the crossover occurs, 3< α <4, the critical exponents vary continuously with the exponent α. We revisit the symbiotic contact process considering a proper method to generate the quasistatiorary state. We perform Monte Carlo simulations on complete and random graphs that are in accordance with the mean-field solutions. Moreover, it is observed hysteresis cycles between the absorbing and active phases with the presence of bistable regions. For regular square lattice, we show that bistability and hysteretic behavior are absence, implying that model undergone a continuous phase transition for any value of the parameter that controlled the symbiotic interaction. Finally, we conjecture that the phase transition undergone by the symbiotic contact process will be continuous or discontinuous if the topology considered is below or above of the upper critical dimension, respectively.